A Regional Perspective on Multinational Expansion Strategies: Reconsidering the Three‐stage Paradigm. (9th May 2013) - Oh, Chang Hoon; Contractor, Farok
Abstract : Empirical studies on international expansion have shown only limited support for the three‐stage (S‐curve) hypothesis. Whilst the basic concept is intuitively acceptable, the very generality of the paradigm is its weakness in empirical studies. This paper takes a more fine‐grained theoretical and empirical approach by distinguishing between the regions covered by different multinational companies. The regional scope covered by a multinational firm makes a substantial difference with regard to its performance. We find that most firms can enhance their performance by focusing on their home region, whilst only a subset of firms operating in both the home and foreign regions show the overall S‐curve relationship between multinationality and performance. Certain combinations of product diversification and regional coverage also enhance performance.